2002
DOI: 10.1177/026010600201600306
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Relationships Between Lifestyle and Diabetes Mellitus, Overweight/Obesity and Hypertension in Nigeria

Abstract: This study of inter-relationship between life styles and diabetes mellitus, overweight/obesity and hypertension was carried out to determine the life styles of the bank workers and the nutritional related diseases. A total sample of 570 was systematically drawn from workers of the United Bank for Africa Plc in Lagos for this study, with the following results. Not surprisingly the level of education influenced life style (P<0.05). There was also a statistically significant relationship between life style and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…[4] It is becoming an emerging disease in Nigeria due to increasing westernization of Nigerian cities and change in lifestyles. [56] A range of cardio-metabolic risk factors such as hypertension and associated disorder of lipid and glucose homeostasis have also been linked to obesity. [5678] The risk of obesity co-morbidities is negligible in normal weight range, mildly increased in overweight, moderately increased in class I obesity (mild obesity), severe in class II obesity (moderate obesity) and very severe in class III obesity (extreme obesity).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[4] It is becoming an emerging disease in Nigeria due to increasing westernization of Nigerian cities and change in lifestyles. [56] A range of cardio-metabolic risk factors such as hypertension and associated disorder of lipid and glucose homeostasis have also been linked to obesity. [5678] The risk of obesity co-morbidities is negligible in normal weight range, mildly increased in overweight, moderately increased in class I obesity (mild obesity), severe in class II obesity (moderate obesity) and very severe in class III obesity (extreme obesity).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity once thought the health problem of affluent Western World now has increased in prevalence in many developing countries such as Nigeria[35610] and has been described as a time bomb for the future explosionin the frequency of cardiovascular diseases, type 2 diabetes mellitus, and dyslipidaemia. [10111213]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that composition of diets and dietary habits among Nigerians have changed towards increased frequency of food consumption, canteen or restaurant eating, snacking as well as lower intakes of fruits and vegetables [18]. This of course could explain the high rate of overweight and obesity observed among participants in the study.…”
Section: Discussionmentioning
confidence: 85%